Adherence to a risk‐adapted screening strategy for prostate cancer: First results of the PROBASE trial. Issue 5 (5th October 2022) - Krilaviciute, Agne; Albers, Peter; Lakes, Jale; Radtke, Jan Philipp; Herkommer, Kathleen; Gschwend, Jürgen; Peters, Inga; Kuczyk, Markus; Koerber, Stefan A.; Debus, Jürgen; Kristiansen, Glen; Schimmöller, Lars; et al.
Abstract: PROBASE is a population‐based, randomized trial of 46 495 German men recruited at age 45 to compare effects of risk‐adapted prostate cancer (PCa) screening starting either immediately at age 45, or at a deferred age of 50 years. Based on prostate‐specific antigen (PSA) levels, men are classified into risk groups with different screening intervals: low‐risk (<1.5 ng/ml, 5‐yearly screening), intermediate‐risk (1.5‐2.99 ng/ml, 2 yearly), and high risk (>3 ng/ml, recommendation for immediate biopsy). Over the first 6 years of study participation, attendance rates to scheduled screening visits varied from 70.5% to 79.4%, depending on the study arm and risk group allocation, in addition 11.2% to 25.4% of men reported self‐initiated PSA tests outside the PROBASE protocol. 38.5% of participants had a history of digital rectal examination or PSA testing prior to recruitment to PROBASE, frequently associated with family history of PCa. These men showed higher rates (33% to 57%, depending on subgroups) of self‐initiated PSA testing in‐between PROBASE screening rounds. In the high‐risk groups (both arms), the biopsy acceptance rate was 64% overall, but was higher among men with screening PSA ≥4 ng/ml (>71%) and with PIRADS ≥3 findings upon multiparameter magnetic resonance imaging (mpMRI) (>72%), compared with men with PSA ≥3 to 4 ng/ml (57%) or PIRADS score ≤ 2 (59%). Overall, PROBASE shows good acceptance of a risk‐adapted PCa screening strategy in Germany. Implementation of such a strategy should be accompanied by a well‐structured communication, to explain not only the benefits but also the harms of PSA screening. Abstract : What's new? Screening for prostate‐specific antigen (PSA) reduces deaths from prostate cancer, but routine PSA screening for all participants leads to overdiagnosis and overtreatment. The PROBASE study, initiated in 2014, uses a risk‐adapted PSA screening strategy that adjusts the screening schedule depending on the participant's initial PSA level. Here, the authors report that adherence rates during the first 6 years of the trial were good, with attendance rates in the 70% to 80% range, and the biopsy acceptance rate was 71% among men with PSA of 4 or higher.